Research on Solving Geometric Problems in College Entrance Examination Mathematics—Take the College Entrance Examination Questions from 2018 to 2022 as an Example - Xiao, Gang; Liu, Min; He, Hongmei (Journal of Research in Vocational Education, 2025)
Analytic geometry is one of the most important and difficult points in the college entrance examination. This paper probes into the analytic geometry in the national paper of mathematics for college entrance examination from 2018 to 2022, and mainly analyzes the conic curve in the analytic geometry in the national paper of mathematics for college entrance examination from horizontal and vertical aspects. In this paper, the real problems in the past 5 years are evaluated from five aspects: content level, background level and reasoning level. Based on Polliats problem-solving theory, this paper studies the problems of trajectory and its equations, fixed-value and fixed-point problems, maximum-value and range problems, and existence problems, provide a reference for teachers teaching.